Futurist approach to the cinema: the investigation of the movie named "Minority Report" - Boyar, Nihan (Istanbul Kultur Univ, Atakoy Campus, Bakirkoy, Istanbul, 34156, Turkey, 2016)
The future phenomenon that the societies see as an expectation is related with the existing power of all the things that are new. Fundamentally, the realization of every new thing could also represent the promise for those to be carried out in the future. On the other hand, the technological gadgets produced nowadays have been adopted by the society and become the necessities of our life styles. Therefore, this increases the desire of the masses for new. As in other fields of art, the concept of futurism, which has idealized the futurism, technology, and every kind of scientific developments, has also emerged in cinema. When considered from this point of view, the fictional technologies created in the movies has been converting into the gadgets that we employ today, and this situation has a great importance in terms of variations in scientific and cultural fields. Thus, in this study, in our age, the reality and usability dimensions of utopian means created as fictional products have been analyzed on the basis of the movie named "Minority Report".
Keywords: Futurism; Reality; Technology; Cinema; Minority Report